Розробка технології бактеріальних препаратів із залученням Lactobacillus сasei ssp. сasei для виробництва функціональних молочних напоїв - Науменко, Оксана Василівна (My University, 2005)
Проведено цілеспрямований відбір з природних джерел штамів молочнокислих бактерій за критеріями функціональної активності та технологічності. Вперше застосовано техніку одержання та регенерації протопластів для селекції штаму лактобацил зі зниженою енергією кислотоутворення. Створено нові для України бактеріальні композиції із залученням біологічно активної культури L. сasei ssp. сasei. Опрацьовано режими та параметри технологічного процесу виробництва бактеріальних препаратів ЛТС і ЛТС-Н для функціонального кисломолочного напою Мілєніум. Досягнуто подовження гарантованого терміну придатності продукту Мілєніум до 14 діб шляхом застосування селекціонованого штаму ацидофільної палички зі зниженою енергією кислотоутворення.

The sorting through lactobacteria strains (by criteria of functional activity and technological effectiveness) from natural sources was conducted. The technique of protoplasts getting and regeneration for the selection of lactobacillus cultures with reduced acidity energy was used for the first time. New for Ukraine bacterial compositions using biologically active culture L. casei ssp. casei were created. Procedures and parametres of technological process of bacterial preparations LTS and LTS-N production for functional lactic acid drink Millenium were created. It was reached an extension of Millenium product shelf-life to 14 days by using selected acidophillus bacillus culture with reduced acidity energy. In laboratory and clinical studies it was proved functional activity of the developed bacterial preparations and products fermented by them. Industrial approbation of bacterial preparations LTS and LTS-N approved their suitability for use as preparations of direct insertion, for products high quality maintenance and their compliance with normative documentation requirements.
Keywords: біотехнологія; функціональний напій; селекція; протопласт; бактеріальні препарати; functional drink; biotechnology; selection; L. casei ssp. casei; protoplast; bacterial drugs